Alphaworld: looking after eggs - Shanahan, Kerrie (Scholastic Canada Ltd. Markham, ON, 2013)
Looking after eggs is crucial for ensuring successful hatching and healthy chicks. It involves maintaining a consistent temperature, typically around 99-102°F, and appropriate humidity levels, usually between 40-50% during incubation, increasing to 60-70% as hatching approaches. Regularly turning the eggs is important to prevent the embryo from sticking to the shell, while good ventilation is necessary to provide oxygen and remove carbon dioxide. Monitoring the eggs for signs of development and adjusting conditions accordingly can greatly enhance the likelihood of successful hatching. Proper care during this critical period ultimately supports the growth of healthy chicks.